The Effect of Branched Chain Amino Acid Supplementation on Stroke-Related Sarcopenia - Park, Min Kyu; Lee, Sook Joung; Choi, Eunseok; Lee, Sangjee; Lee, JungSoo (Frontiers in Neurology, 2022)
Background Stroke-related sarcopenia occurs in consideration of multi-factors, such as brain damage, systemic catabolic state, skeletal muscle imbalance, and malnutrition. In the long-term care plan after stroke, appropriate rehabilitation strategies to achieve maximum functional improvement and to prevent the development of sarcopenia are important. This study investigated the effect of branched chain amino acid (BCAA) supplementation on sarcopenia after stroke. We also evaluated the effect of BCAA on functional improvement during the intensive rehabilitation period. Methods Subacute stroke patients who had stroke-related disabilities were enrolled and given dietary supplement powder containing BCAAs for 1 month. These BCAAs were as supplied through the nutrition team during feeding time. Patients whose age, sex and stroke lesions were similar to those of the study group were enrolled in the control group through medical record review. Both groups received personalized intensive inpatient rehabilitation therapy in a single unit rehabilitation center. All patients’ target calories were calculated regularly by the Nutritional Support Team in our institution. Sarcopenia status was evaluated by using grip strength and skeletal muscle index (SMI) which was assessed by dual energy X-ray absorptiometry (DEXA). Functional status associated with stroke were evaluated every month, including activities of daily living, balance, gait, and swallowing. Results Fifty-four patients were enrolled 27 patients each of the two groups. The study group showed significantly greater improvement of SMI after intervention than the control group. Both groups exhibited functional improvement over time, but the improvement in the study group was significantly greater than that in the control group. Univariate analysis revealed that patients with better functional status had a greater SMI with a combination of BCAA supplementation and intensive rehabilitation therapy. Conclusion Our results showed a positive effect of BCAA supplementation on sarcopenia after stroke. We also found that nutritional support helps functional improvement during neurologic recovery. These results suggest that comprehensive rehabilitation intervention combined with BCAA supplementation could be a helpful option during the critical period for post-stroke neurologic recovery.